PERANCANGAN WEBSITE MAKANAN BERNAMA TASTYFOOD DENGAN MENGGUNAKAN FRAMEWORK LARAVEL - Ahmad Setiawan, Rizal; Suwartika, Rini (INFOKOM (Informatika & Komputer), 2024)
Tastyfood is a website that can provide information about food, especially typical Indonesian food, which is food that comes from our homeland, Indonesia. This website aims to make it easy for people to access information about Indonesian food. This research was created using the Laravel framework. The method used is with a prototype methodology that contains use cases and activity diagrams in it, the implementation of its creation uses PHP and CSS Bootstrap with blackbox testing, with the results of a website that has a display that has quite a lot of images and of course makes it easier to disseminate information.